The effects of zinc sulphate administration to pregnant sheep on some biochemical parameters in blood sera of sheep and its lambs, and birth weights of lambs - Çimtay, I; Sahin, T; Aksoy, G; Olçücü, A (M H Schaper Gmbh Co Kg, 2001)
The aims of this study were to demonstrate the effects of zinc sulphate administration (2 g/week PO, 2% solution) on zinc, copper, iron, calcium and magnesium levels in blood serum of 20 pregnant Ivesi sheep during the last 2 month of pregnancy, immediately post partum as well as in their newborn lambs. In these 20 lambs, also total serum protein, gamma globulin and birth weight were determined. The control group consisted of 15 pregnant sheep and their 15 Iambs housed under the same conditions. Zinc sulphate administered to sheep caused significant increases in their serum levels of zinc as well as in those of their lambs. The lambs of the zinc supplemented group had also slightly higher birth weights (not significant) and significant higher gamma globulin levels, whereas the total protein values was almost identical in both groups.
Auswirkungen einer oralen zinksubstitution auf einige biochemische serumparameter bei trächtigen schafen und deren lämmern sowie auf die geburtsgewichte der lämmer
Keywords: sheep; lamb; zinc administration; biochemical parameters; birth weight